Electroluminescence of ultraviolet and thermally aged low density polyethylene - Mills D.H.; Lewin P.L.; Chen G.; Ariffin A.M. (2023)
It has been postulated that long term ageing of lowdensity polyethylene (LDPE) is due to the movement of space charge within the dielectric. Electroluminescence (EL) has been shown as an alternative method to investigate charge movement within a dielectric. Under ac fields, EL is related to the injection, trapping and recombination of charge carriers at the sample interface. This work investigates the change in EL emission due to the ultraviolet (UV) ageing of additive free 100?m LDPE films. Samples are aged in an oven using a 36W UV fluorescent tube at a temperature of 313K. This causes bond breakages and increased carbonyl and hydroxyl groups as confirmed by Fourier transform infrared (FTIR) spectroscopy. Weibull breakdown statistics also show an increasing reduction in the ac ramp breakdown strength with ageing time. EL images and temporal measurements are collected using a deep cooled charge coupled device (CCD) camera and show an initial reduction in the EL with ageing. Further ageing shows a field dependence of the EL. 2010 IEEE.